IMPLEMENTATION OF DESIGN AND DEVELOPMENT TENSILE TESTING MACHINEFOR APPLICATION IN SOFT MATERIAL TESTING - Baharuddin Baharuddin; Yani Yani (Program Pascasarjana Universitas Negeri Jakarta, 2018)
Current technological developments produce various kinds of innovations and creations in all things, which goal to facilitate all human activities. There are various kinds of tools for testing, ranging from tensile testing, compressive testing and hardness testing. In this case, this research designs and develops miniature tensile test kits. Our goal is to do tensile testing to find out the yield strength, elongation, tensile strength and elastic modulus. This tensile test equipment is designed using a servo motor with 3 AC inputs, 105 V, 0.7 A with 100 watt output and 3000 rad / min motor rotation comparable (477.46 rpm), power transfer using fan belt. This servo motor is controlled by a servo amplifier that goal is to send a signal to control the motor speed, motor rotation direction. The servo amplifier is then connected to a laptop / computer to regulate the amplifier, and describes the test results in the form of stress and strain graphs that occur in tensile test specimens. The component components of the tensile test equipment analyzed in this study are; specimen pin, grip and grip holder). The goal is to determine the maximum stress that occurs so it can be categorized as safe or not used for testing aluminium (Al) and Copper (Cu) specimens. To find out the component is safe or not with the help of the Solid works 2014 software. By analyzing the maximum von Mises stress that occurs in each component analyzed for use in aluminium (Al) and Copper (Cu) specimens.